Lunch money eaudiobook - Clements, Andrew (Listening Library, 2005)
Greg had started looking around the cafeteria, and everywhere he looked, he saw quarters. He saw kids trading quarters for ice cream sandwiches and cupcakes and cookies at the dessert table. He saw kids over at the school store trading quarters for neon pens and sparkly pencils, and for the little decorations like rubber soccer balls and plastic butterflies to stick onto the ends of those new pencils…. There were quarters all over the place, buckets of them. At that moment Greg’s view of school changed completely and forever. School had suddenly become the most interesting place on the planet. Because young Greg Kenton had decided that school would be an excellent place to make his fortune.